2020
DOI: 10.3390/app10238654
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of Continuous Beams Made of Self-Compacting Concrete (SCC)—Experimental and Numerical Analysis

Abstract: Self-compacting concrete (SCC) is a type of concrete that is placed in the formwork under its own weight. Although there are many studies showing the behavior of SCC beams, most relate to the behavior of simple supported beams. Unlike those, this is a study of continuous beams made of SCC aimed to analyze their flexural performance as well as to confirm the possibility of using nonlinear finite element analysis (FEA) in the design of such structural elements. An experimental study of three two-span continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Additionally, Luo et al [22] and Huang et al [23] suggested that the failure form of self-compacting concrete (SCC) beams is similar to that of NC beams, whereas the ultimate bending moment of SCC beams is slightly larger than that of NC beams; moreover, the cracking moment of SCC beams is slightly smaller. Petrovic et al [24] found that SCC beams had satisfactory bearing capacity and stiffness, confirming the possibility of using SCC in continuous beams. Xue et al [25] found that the ultimate bearing capacity of SCC beams can be calculated using the current code equations.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Additionally, Luo et al [22] and Huang et al [23] suggested that the failure form of self-compacting concrete (SCC) beams is similar to that of NC beams, whereas the ultimate bending moment of SCC beams is slightly larger than that of NC beams; moreover, the cracking moment of SCC beams is slightly smaller. Petrovic et al [24] found that SCC beams had satisfactory bearing capacity and stiffness, confirming the possibility of using SCC in continuous beams. Xue et al [25] found that the ultimate bearing capacity of SCC beams can be calculated using the current code equations.…”
Section: Introductionmentioning
confidence: 87%
“…These material properties of recycled aggregate can also affect the performance of the components. So far, the flexural properties of recycled aggregate concrete (RAC) beams [14][15][16][17][18][19][20][21] and SCC beams [22][23][24][25][26] have been experimentally studied, and valuable results have been obtained. Ignjatovic et al [14] found no significant difference between the load-deflection curves and ultimate bearing capacity of RAC beams and normal concrete (NC) beams.…”
Section: Introductionmentioning
confidence: 99%
“…The adopted CDP model introduces damage of the concrete both due to compression and tension, and has its ground in Fracture mechanics, i.e., on the Drucker-Prager's hyperbolic function of flow of the plastic potential. Taking into account [23], this model has been selected as adequate for modelling quasi-brittle materials, see also [26,27]. Prior to applying the CDP material model in analysis, several input parameters need to be defined, as described below.…”
Section: Explicit Dynamics Fe Analysis Using the Concrete Damage Plas...mentioning
confidence: 99%
“…Dilatation angle (dilatancy) ψ has been adopted as ψ = 30°, according to [27]. For the eccentricity of the plastic potential є, and for the relation between the biaxial and uniaxial yield stress under compression σ b0 /σ c0 , default values have been chosen, i.e., є = 0.1 and σ b0 /σ c0 = 1.16, as recommended in [26].…”
Section: Explicit Dynamics Fe Analysis Using the Concrete Damage Plas...mentioning
confidence: 99%
See 1 more Smart Citation